Understanding perioperative bowel preparation for colorectal surgery - Zhou, Xuefu; He, Yulong (Digestive Medicine Research, 2020)
Bowel preparation is an important perioperative measure in elective colorectal surgery. The goal is to empty the contents of the intestine and reduce the number of bacteria in the intestine, so as to reduce the risk of surgical-related infections, ensure the safety of the surgery and facilitate a smooth postoperative recovery. Compared with the upper abdominal surgery, colorectal surgery is usually associated with a higher risk of postoperative infection, including incision and abdominal infections, anastomotic leakage and infection-related intestinal obstruction, and of infections of distant organs, such as pneumonia and urinary tract infections. With the application of evidence-based medicine in clinical practice, especially the popularization of enhanced recovery after surgery (ERAS), the unfavorable factors of bowel preparation, such as physical discomfort, interference with normal physiology, and increased care burden, have received increasing attention. Relevant clinical trials and meta-analyses continue to emerge, and the clinical significance of bowel preparation in preventing postoperative infection has been questioned.